A method for preparing high-strength ceramic green body at low temperature by adding molybdenum slag and rubidium tailings and its product
By adding molybdenum slag and rubidium tailings into ceramic materials, and adopting low-value-added minerals and fusion-supported multi-systems to optimize formulas and processes, the problems of high energy consumption and pollution of ceramic materials are solved, and high-strength and low-energy consumption of ceramic products are achieved.
Patent Information
- Application Number
- CN202311584602.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-11-26
AI Technical Summary
Existing ceramic materials have challenges in performance and production costs, including high pollution, high energy consumption and high emissions, and it is difficult to effectively utilize industrial solid waste as raw materials for porcelain making.
By incorporating molybdenum slag and rubidium tailings, combining low-value-added minerals and fusion-supported multi-systems, the formulation composition and process parameters are optimized, and low-temperature firing technology is used to reduce the firing temperature and energy consumption of ceramic products.
It realizes high-strength and low-energy production of ceramic materials, reduces production costs and environmental hazards, and provides a resource utilization solution for industrial solid waste.
Smart Images

Figure CN117550875B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings, and a product thereof. Background Art
[0002] With the acceleration of industrialization, the ceramic industry has developed rapidly. my country has become the world's largest ceramic producer, with products exported to more than 160 countries and regions. The annual export volume and amount rank first in the world. The ceramic industry has gradually become an important industry in my country's national economy and a new driving force for regional economic development. However, the current situation of high pollution, high energy consumption and high emissions in the ceramic industry seriously restricts the development of the industry. At present, in addition to pursuing light weight, high strength and low water absorption in terms of performance, how to reduce production costs is also a focus of the ceramic industry. This includes two aspects. One is to use tailings or waste generated in related fields such as the ceramic industry, metallurgical industry, and construction industry to save raw material costs; the other is to reduce the firing temperature on the basis of ensuring the strength of the green body to reduce energy consumption.
[0003] The chemical composition of industrial solid waste is mostly characterized by "high silicon, high aluminum, and rich alkali", which has certain similarities with ceramic components. Considering that it is classified as a barren raw material, if an appropriate amount of low-value-added clay mineral raw materials is added to the formula, it can well realize the transformation of waste into treasure and alleviate the current situation of mineral resource depletion. Furthermore, if the firing temperature is reduced by 100°C, 10-15% of fuel can be saved. In addition to reducing production energy consumption, it can also shorten the firing time and increase production capacity. Based on the above analysis, if industrial solid waste such as molybdenum slag and rubidium tailings can be fully utilized as porcelain raw materials, and the formula composition and raw materials can be experimentally optimized, so that ceramic materials can be sintered at low temperatures, it can not only realize the resource utilization of industrial solid waste and reduce the harm to the environment, but also improve the "three highs" situation that restricts the development of the industry, with very significant economic benefits.
[0004] The factors that restrict the strength of ceramic materials are mainly elastic modulus, crack size and fracture surface energy. Therefore, considering these three aspects, the main ways to strengthen ceramic green bodies in the existing technology can be divided into improving the sintering degree of the porcelain body, reducing the defects on the surface and inside of the ceramic products, introducing reinforcing phases and prestressing reinforcement, but most of these reinforcement methods have a series of problems such as limited improvement, high difficulty in operation and inability to mass produce. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings. By adding solid waste and low value-added minerals, optimizing the formula composition and process parameters experimentally, and using a Rb-K-Na-Ca-Mg-Fe composite fluxing multi-element system, the firing temperature of ceramic products is greatly reduced and the firing temperature range is widened. The strength of the ceramic material is effectively improved by in-situ generation of a crystalline phase, thereby achieving the purpose of reducing energy consumption and being green and environmentally friendly. Another purpose of the present invention is to provide a product prepared by the above-mentioned preparation method.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings. The raw materials of the ceramic body are composed of 17-23wt% of kaolin, 8-11wt% of quartz sand, 16-20wt% of silty shale, 10-16wt% of molybdenum slag, 7-9wt% of potassium feldspar, 8-10wt% of wollastonite, 9-11wt% of burned talc and 11-16wt% of rubidium tailings. The preparation method comprises the following steps:
[0008] (1) The raw materials are weighed according to the ratio, and then wet ball milled to obtain a slurry, which is then dried, ground, and sieved to obtain a particle size distribution D 50 3.7~6.8μm, D 90 Powdered materials with a size of 7.3 to 15.2 μm;
[0009] (2) After the powder material is pressed and formed, the temperature is increased from room temperature to 1080-1120° C. at a heating rate of 10-20° C. / min, and the temperature is kept at that temperature for 30-90 min. After the temperature is kept at that temperature, the powder material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding molybdenum slag and rubidium tailings.
[0010] Furthermore, the particle size of each component of the raw material of the present invention is 60-100 mesh. The time of wet ball milling in step (1) is 40-120 minutes. The pressure of pressing in step (2) is 10-12 MPa, and the pressing time is 20-40 seconds.
[0011] Furthermore, the chemical composition of the molybdenum slag of the present invention is SiO2 65.39-76.38wt%, Al2O3 9.27-14.29wt%, K2O 2.24-6.62wt%, Na2O 1.04-2.74wt%, MgO 0.61-1.75wt%, CaO 1.21-2.95wt%, Fe2O3 1.21-3.72wt%, TiO2 0.01-1.42wt%, and loss on ignition 1.27-2.75wt%; the chemical composition of the rubidium tailings is SiO2 45.38-57.64wt%, Al2O3 10.39-22.14wt%, K2O 0.84-3.12wt%, Na2O 0.85-2.94wt%, MgO 0.71-2.83wt%, CaO 0.67~2.48wt%, Fe2O32.14~7.68wt%, TiO20.01~1.09wt%, Rb2O 0.35~1.14wt%, ignition loss 0.02~12.65wt%.
[0012] The product is prepared by the method of preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings. The crystal phase composition and content of the ceramic body are 38.3-42.1% of anorthite, 8.7-11.6% of quartz, and 7.8-9.1% of diopside; the flexural strength of the ceramic body is 91.7-114.3MPa, the water absorption rate is 0.06-0.23%, and the volume density is 2.48-2.50g / cm 3 , the open porosity is 0.33~0.55%.
[0013] The present invention has the following beneficial effects:
[0014] (1) The fluxing oxides contained in molybdenum slag, potassium feldspar, wollastonite, calcined talc and rubidium tailings are eutectic at high temperature to form a Rb-K-Na-Ca-Mg-Fe composite fluxing system, which greatly reduces the sintering temperature of the green body, promotes the formation of liquid phase at a lower temperature, advances the nucleation and growth process of the crystal, and is beneficial to increase the content of the crystalline phase in the green body and the size of the crystal.
[0015] (2) The molybdenum slag, silty shale, rubidium tailings and quartz sand of the present invention all contain a large amount of SiO2 components, which can not only make more quartz melt into the liquid phase to participate in the synthesis process of anorthite and diopside crystal phases under the action of the Rb-K-Na-Ca-Mg-Fe composite flux, but also increase the content of quartz crystal phase in the green body in this formulation system. The particle dispersion toughening effect of the blocky quartz crystals and the anorthite and rod-shaped diopside crystals interspersed therein form a three-dimensional network structure, thereby greatly increasing the strength of the ceramic material.
[0016] (3) The present invention has a simple operation process, low cost and is easy to control. By optimizing the raw material ratio and formulation system, the firing temperature of ceramic products is greatly reduced and the firing temperature range is widened. The in-situ generation of crystal phases is adopted to effectively improve the strength of ceramic materials, which is beneficial to thinning the thickness of ceramic materials and achieving the actual requirements of energy conservation and consumption reduction. At the same time, it also provides a reasonable and effective utilization plan for the research on solid wastes such as molybdenum slag and rubidium tailings, and low-value-added minerals such as siltstone in the preparation of ceramic materials, which is of great significance in reducing energy consumption and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings:
[0018] Figure 1 is a scanning electron microscope image of a ceramic body prepared in an embodiment of the present invention;
[0019] Figure 2 The figure is the XRD spectrum of the ceramic body prepared in the embodiment of the present invention. DETAILED DESCRIPTION
[0020] Embodiment 1:
[0021] The present embodiment provides a method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings. The raw materials of the ceramic body are 23wt% kaolin, 11wt% quartz sand, 20wt% silty shale, 10wt% molybdenum slag, 8wt% potassium feldspar, 8wt% wollastonite, 9wt% calcined talc, and 11wt% rubidium tailings. The particle size of each raw material component is 60-100 meshes. The preparation method has the following steps:
[0022] (1) The above raw materials were weighed according to the ratio, and then wet-milled for 40 min at a ratio of material: ball: water = 1:2:1 to obtain a slurry. The obtained slurry was dried at 100°C for 6 h, ground, and passed through a 120-mesh standard sieve to obtain a particle size distribution D 50 6.8μm, D 90 Powdered materials with a diameter of 15.2 μm;
[0023] (2) The powdered material is pressed into shape at a pressure of 10 MPa for 20 seconds; after the pressing, the temperature is increased from room temperature to 1080°C at a heating rate of 10°C / min for sintering, and the temperature is kept for 90 minutes. After the temperature is kept, the powdered material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding molybdenum slag and rubidium tailings.
[0024] Embodiment 2:
[0025] The present embodiment provides a method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings. The raw materials of the ceramic body are 21wt% kaolin, 9wt% quartz sand, 18wt% silty shale, 12wt% molybdenum slag, 9wt% potassium feldspar, 9wt% wollastonite, 10wt% calcined talc, and 12wt% rubidium tailings. The particle size of each raw material component is 60-100 meshes. The preparation method has the following steps:
[0026] (1) The above raw materials were weighed according to the ratio, and then wet-milled for 70 min at a ratio of material: ball: water = 1:2:1 to obtain a slurry. The obtained slurry was dried at 100°C for 6 h, ground, and passed through a 150-mesh standard sieve to obtain a particle size distribution D 50 5.9μm, D 90 Powdered material of 10.4μm;
[0027] (2) The powdered material is pressed into shape at a pressure of 12 MPa for 30 seconds; after the pressing, the temperature is raised from room temperature to 1100°C at a heating rate of 15°C / min for sintering, and the temperature is kept for 60 minutes. After the temperature is kept, the powdered material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding molybdenum slag and rubidium tailings.
[0028] Embodiment three:
[0029] The present embodiment provides a method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings. The raw materials of the ceramic body are 18wt% kaolin, 9wt% quartz sand, 17wt% silty shale, 14wt% molybdenum slag, 8wt% potassium feldspar, 8wt% wollastonite, 11wt% calcined talc, and 15wt% rubidium tailings. The particle size of each raw material component is 60-100 meshes. The preparation method has the following steps:
[0030] (1) The above raw materials were weighed according to the ratio, and then wet-milled for 100 min at a ratio of material: ball: water = 1:2:1 to obtain a slurry. The obtained slurry was dried at 100°C for 6 h, ground, and passed through a 180-mesh standard sieve to obtain a particle size distribution D 50 4.3μm, D 90 Powdered materials with a particle size of 8.8 μm;
[0031] (2) The powdered material is pressed into shape at a pressure of 10 MPa for 40 seconds; after the pressing, the temperature is raised from room temperature to 1110°C at a heating rate of 15°C / min for sintering, and the temperature is kept for 30 minutes. After the temperature is kept, the powdered material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding molybdenum slag and rubidium tailings.
[0032] Embodiment 4:
[0033] The present embodiment provides a method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings. The raw materials of the ceramic body are 17wt% kaolin, 8wt% quartz sand, 16wt% silty shale, 16wt% molybdenum slag, 7wt% potassium feldspar, 10wt% wollastonite, 10wt% calcined talc, and 16wt% rubidium tailings. The particle size of each raw material component is 60-100 mesh. The preparation method has the following steps:
[0034] (1) The above raw materials were weighed according to the ratio, and then wet-milled for 120 min at a ratio of material: ball: water = 1:2:1 to obtain a slurry. The obtained slurry was dried at 100°C for 6 h, ground, and passed through a 200-mesh standard sieve to obtain a particle size distribution D 50 3.7μm, D 90 Powdered material of 7.3μm;
[0035] (2) The powdered material is pressed into shape at a pressure of 12 MPa for 40 seconds; after the pressing, the temperature is raised from room temperature to 1120°C at a heating rate of 20°C / min for sintering, and the temperature is kept for 90 minutes. After the temperature is kept, the powdered material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding molybdenum slag and rubidium tailings.
[0036] The chemical composition of the raw materials of the ceramic green body of the embodiment of the present invention is shown in Table 1.
[0037] Table 1 Chemical composition of ceramic raw materials of the present invention (wt%)
[0038]
[0039] The ceramic body prepared in the embodiment of the present invention has a crystal phase composed of calcium feldspar, quartz, diopside (see Figure 2 );like Figure 1 As shown, it has a morphological structure with blocky quartz crystals and rod-shaped diopside crystals interspersed therein.
[0040] The ceramic green body without adding molybdenum slag and rubidium tailings is used as a comparative example (other conditions are the same as those of Example 1). The performance tests of the ceramic green bodies prepared in the examples of the present invention and the comparative examples are shown in Table 2.
[0041] Table 2 Performance indicators of ceramic bodies of the embodiments of the present invention and comparative examples
[0042]
[0043] The results in Table 2 show that the sintering degree of the ceramic body in the comparative example without adding the molybdenum slag and rubidium tailings system is not high, and there are problems such as high porosity, high water absorption, low bulk density and low flexural strength. The embodiment of the present invention can not only achieve low-temperature sintering under the molybdenum slag and rubidium tailings system, but also has performance indicators far higher than the flexural strength ≥35MPa and water absorption ≤0.5% specified in the national standard GB / T4100-2015, and is also significantly better than the comparative example, further reducing the raw material cost and energy consumption, and achieving the actual requirements of lightweight ceramic materials and energy saving and consumption reduction.
Claims
1. A method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings, characterized in that: The raw material composition of the ceramic body is kaolin 17-23wt%, quartz sand 8-11wt%, silty shale 16-20wt%, molybdenum slag 10-16wt%, potassium feldspar 7-9wt%, wollastonite 8-10wt%, calcined talc 9-11wt%, rubidium tailings 11-16wt%; wherein the chemical composition of the molybdenum slag is SiO2 65.39-76.38wt%, Al2O3 9.27-14.29wt%, K2O 2.24-6.62wt%, Na2O 1.04-2.74wt%, MgO 0.61-1.75wt%, CaO 1.21-2.95wt%, Fe2O31.21-3.72wt%, TiO20.01-1.42wt%, loss on ignition1.27-2.75wt%; the chemical composition of the rubidium tailings is SiO245.38-57.64wt%, Al2O310.39-22.14wt%, K2O 0.84-3.12wt%, Na2O 0.85-2.94wt%, MgO 0.71-2.83wt%, CaO 0.67-2.48wt%, Fe2O32.14-7.68wt%, TiO20.01-1.09wt%, Rb2O 0.35-1.14wt%, loss on ignition0.02-12.65wt%; the particle size of each component of the raw materials is 60-100 mesh; the preparation method comprises the following steps: (1) The raw materials are weighed according to the ratio, and then wet ball milled to obtain a slurry, which is then dried, ground, and sieved to obtain a particle size distribution D 50 3.7~6.8μm, D 90 Powdered materials with a size of 7.3 to 15.2 μm; (2) After the powder material is pressed and formed, the temperature is raised from room temperature to 1080-1120° C. at a heating rate of 10-20° C. / min, and the temperature is kept for 30-90 minutes. After the temperature is kept, the material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding molybdenum slag and rubidium tailings; the crystal phase composition and mass percentage content of the ceramic body are 38.3-42.1% of calcium feldspar, 8.7-11.6% of quartz, and 7.8-9.1% of diopside, and the particle dispersion toughening effect of the blocky quartz crystals and the calcium feldspar and rod-shaped diopside crystals are interspersed therein to form a three-dimensional network structure; the flexural strength of the ceramic body is 91.7-114.3 MPa, the water absorption rate is 0.06-0.23%, and the volume density is 2.48-2.50 g / cm 3 , the open porosity is 0.33~0.55%.
2. The method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings according to claim 1, characterized in that: The time of wet ball milling in step (1) is 40 to 120 minutes.
3. The method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings according to claim 1, characterized in that: The pressure of the pressing process in step (2) is 10-12 MPa, and the pressing time is 20-40 s.
4. A product obtained by the method for preparing a high-strength ceramic body at low temperature by adding molybdenum slag and rubidium tailings as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Low-temperature fired high-strength building ceramic green body and preparation method thereof
CN114349492A
Method for preparing building ceramic green body at low temperature by adopting low-aluminum raw material and product thereof
CN114455938A